2019
DOI: 10.20448/journal.509.2019.64.156.161
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Turtle Mobile Learning Application for Scientific Literacy in Elementary School

Abstract: Turtles are animals vulnerable to extinction. Scientific literacy is the main goal of the science curriculum. Augmented Reality technology is very helpful in the education process of animal conservation. Turtle mobile learning is one of the scientific literacy sources developed on Android smartphones. The study's purpose is to produce and determine the effectiveness of turtle mobile learning media to develop the students' scientific literacy about Sumatran turtle conservation. The study used Research and Devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
1
6
0
2
Order By: Relevance
“…The observation result in the process skills aspect in students' experiment activity showed good criteria. The experiment showed that students could understand the lesson easily and acquire improved motivation to seek new concepts (Winarni & Purwandari, 2019). It was related to (Marks & Eilks, 2009) who stated that the learning situation which was conducted by the students and the teacher interestingly would be successful in increasing the students' science literacy.…”
Section: B the Process Skill Of Students' Science Literacymentioning
confidence: 86%
“…The observation result in the process skills aspect in students' experiment activity showed good criteria. The experiment showed that students could understand the lesson easily and acquire improved motivation to seek new concepts (Winarni & Purwandari, 2019). It was related to (Marks & Eilks, 2009) who stated that the learning situation which was conducted by the students and the teacher interestingly would be successful in increasing the students' science literacy.…”
Section: B the Process Skill Of Students' Science Literacymentioning
confidence: 86%
“…The presence of this virtual laboratory is undoubtedly expected to support students' learning practicums, as it is known that practicum activities or simulations in a virtual environment in the current era can effectively involve students (Kamińska et al, 2019). According to several research reports, virtual laboratories can increase students' scientific literacy (Winarni & Purwandari, 2019) and improve learning outcomes (Wahyuman et al, 2021). Increasing literacy and skills for students is very important because it will help them train their thinking skills and be competitive in the era of globalization.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between literacy is that someone who has scientific literacy is willing to discuss science and technology discourse [16]. It requires competence to (1) explain scientific phenomena: acknowledge, offer, and evaluate explanations for various natural phenomena and technology; (2) evaluating and designing scientific research: describing and evaluating scientific investigations, and proposing ways of dealing with scientific questions; and (3) interpreting scientific data and evidence: analyzing and evaluating data, claims, and arguments in various representations and drawing appropriate scientific conclusions.…”
Section: Health Literacymentioning
confidence: 99%